The public, the private, and the business-societal: A threefold approach to business responsibility for human rights - Mende, Janne (Edward Elgar Publishing, 2020)
Overall, the role of business companies for the violation, but also for the protection of human rights has become a pivotal research agenda across the disciplines. Since the 1990s, debates increasingly focus on the question, whether, and if so to what extent, companies as private actors can be held responsible for human rights. This question challenges the international human rights system that holds states as public actors responsible for the respect, protection and fulfilment of human rights. Against this background, this paper argues that the conceptual frame of public and private does not suffice to capture business roles for human rights in times of global governance and globalisation. Instead, it suggests a threefold approach to the public, the private, and the business-societal.